Thermosensitive Block of the Sabin Strain of Poliovirus Type I - Fiszman, Marc (1972)
The thermosensitive defect of the Sabin LSc2ab strain of poliovirus type I was studied. Transfer of infected KB cells from 36 to 38.5 C resulted in 30% inhibition of viral RNA replication but in 90% inhibition of formation of virions. Neither 74S procapsids nor 14S particles were detected in the cells transferred to the non-permissive temperature. However, procapsids, once accumulated at 36 C, were normally stable at 38.5 C and could transform into virions at that temperature. Viral proteins synthesized at the nonpermissive temperature were not different from those synthesized at permissive temperature, as judged from their pattern in polyacrylamide gel electrophoresis and from the fact that they normally matured into virions when the infected cells were brought back to permissive temperature, even under conditions of inhibition of protein synthesis. This leads to the conclusion that the defect in the Sabin strain studied lies in the assembly of its viral capsid proteins into capsomeres.